Regional Economic Outlook, October 2014, Middle East and Central Asia,. (Regional Economic Outlook, 2014)
This issue discusses economic developments in the Middle East, North Africa, Afghanistan, and Pakistan (MENAP), which continue to reflect the diversity of conditions prevailing across the region. Most high-income oil exporters, primarily in the GCC, continue to record steady growth and solid economic and financial fundamentals, albeit with medium-term challenges that need to be addressed. In contrast, other countries-Iraq, Libya, and Syria-are mired in conflicts with not only humanitarian but also economic consequences. And yet other countries, mostly oil importers, are making continued but uneven progress in advancing their economic agendas, often in tandem with political transitions and amidst difficult social conditions. In most of these countries, without extensive economic and structural reforms, economic prospects for the medium term remain insufficient to reduce high unemployment and improve living standards.